Empowering MGMP of Central Maluku German Language in Developing AKM Literacy Instruments - Serpara, Henderika; Wenno, Eldaa Crystle; Karuna, Kalvin (Unram Journal of Community Service, 2024)
The German Language MGMP (Musyawarah Guru Mata Pelajaran) empowerment program in Central Maluku has a clear goal in the development of literacy AKM (Minimum Competency Assessment) instruments. The program begins with an introduction to what an AKM instrument is and its importance in measuring literacy skills in German. Participants were introduced to the framework and methods of AKM instrument development. This community service program aims to: (1) improve the skills of German language teachers in Central Maluku in developing literacy AKM instruments; (2) increase collaboration among teachers and build networks and cooperation to create active and connected German language teachers, and allied teachers, so that they can share experiences, resources, and best practices. The methods used are: (a) initial observation; (b) plan development; (c) online and offline face-to-face approach with teachers; (d) training; (e) evaluation. This activity is carried out face-to-face directly (offline) and indirectly (online). The results achieved from the Central Maluku German Language MGMP empowerment activities in developing literacy AKM instruments show that these efforts have succeeded in improving teacher competence in designing and implementing assessment instruments. The training and workshops not only strengthened teachers' understanding of AKM, but also enriched German teaching methods, encouraged collaboration between teachers and cognate teachers and resulted in the exchange of ideas and best practices in learning.